Efetividade dos direitos fundamentais das mulheres negras: uma abordagem na perspectiva do colorismo e de políticas de ações afirmativas - Figueiredo, Maria Vitória Silva (2024)
The present study aims, through a historical-social contextualization of the place of Black women in Brazilian society, to analyze the legislation and public policies for the promotion of racial equality, as well as the challenges that hinder the full implementation and effectiveness of affirmative actions, such as racial quotas. To achieve this, an analysis will be conducted based on the instrumental concept of colorism, contributing to a greater understanding of the complexity of the racism issue in our country, particularly regarding women. The study will explore sensitive topics such as miscegenation and eugenics, identifying the stereotypes and racism faced by light-skinned Black women and their consequent impact on access to rights and public policies. Additionally, international instruments and norms, both global and regional, as well as provisions of the 1988 Federal Constitution that address this theme, and infraconstitutional legislation, especially concerning the social inclusion of Black women in the post-Abolition period, will be analyzed. Furthermore, the study intends to examine the mechanisms for evaluating and validating access to affirmative actions, such as self-identification and heteroidentification, and the phenomena involving the questioning of the racial identity of mixed-race individuals, as well as fraud in racial quotas, presenting new perspectives and a practical proposal for the effective inclusion of mixed-race women in social structures and their identity recognition. This will contribute to the enhancement of processes for verifying the racial identity of light-skinned Black women and the consequent optimization of affirmative actions aimed at this purpose